Professional ideals and daily practice in journalism. (April 2015) - Pihl-Thingvad, Signe
Professional ideals are crucial in terms of guiding and committing journalists in modern media organizations. But what happens if there are discrepancies between the journalists' professional ideals and their daily working practice? Research suggests negative consequences, such as withdrawal of commitment, but until now these assumptions have never been empirically examined. This article provides new knowledge of the relationship between professional ideals and daily practice in journalism by describing the contours of the existing discrepancies in the generation of news in Denmark. In addition it examines the journalists' reactions to discrepancies in relation to their organizational commitment. The results suggest that discrepancies do have a negative impact on journalists' commitment. Further implications for research and practice of the findings are discussed.